IMPLEMENTASI KURIKULUM MERDEKA DALAM MENINGKATKAN MUTU PENDIDIKAN - Ujang Cepi Barlian,; Siti Solekah,; puji rahayu, (JOEL: Journal of Educational and Language Research, 2022)
The curriculum is the "spirit" of education that must be innovative, dynamic, and periodically in accordance with the times and science and technology, competencies needed by the community and graduate users. According to Oliva as quoted by Din Wahyudin (2014: 6), the curriculum is seen as a goal, context and strategy in learning through a program of developing instruments or learning materials, social interaction and systematic learning techniques in educational institutions. Curriculum changes to ensure that the learning process in schools/madrasahs becomes better. Curriculum change – thus – is a necessity. The Ministry of Education, Culture, Research, and Technology (Kemendikburistek) issued a policy in the development of the Independent Curriculum which was given to education units as an additional option in order to restore learning during 2022-2024 and improve the quality of education. Therefore, this article describes the Implementation of the Independent Curriculum in improving the Quality of Education implemented at SDN 244 Guruminda. This research uses an approach approach, in collecting data using participatory observation, study documentation, and interviews. In this study, there are 3 aspects in the implementation of the independent curriculum, namely planning for the implementation of the independent curriculum, implementing the independent curriculum and evaluating the learning of the independent curriculum. Independent curriculum planning at SDN 244 Guruminda is carried out by analyzing learning outcomes (CP) to formulate learning objectives and flow of learning objectives, planning diagnostic assessments, developing learning modules that adapt learning to the stage of achievement and characteristics of students and planning formative and summative assessments. Implementation of the independent curriculum at SDN 244 Guruminda by carrying out diagnostic assessments, carrying out learning according to project-based teaching modules, as well as implementing formative and summative assessments. Evaluation of learning in the implementation of the independent curriculum at SDN 244 Guruminda by carrying out diagnostic assessments, implementing and processing formative and summative assessments. The author suggests that SDN 244 Guruminda Bandung City continue to monitor and develop themselves by continuing to improve the curriculum for better school quality, besides that the success of schools in implementing independence is disseminated to schools that have not implemented independence.